Analysis on the performance of a three-phase cascaded H-bridge multilevel inverter - Azli, N. A.; Choong, Y. C. (2006)
Previous works have pointed out the limitations of conventional inverters especially in high voltage and high power applications. In recent years, multilevel inverters are becoming increasingly popular for high power applications due to its improved harmonic profile and increased power ratings. Works on the aspect of topology, control techniques and applications of multilevel inverters have been reported in literatures. However, there are no concrete findings that actually discuss or evaluate the performance of a three-phase multilevel inverter. This paper presents some analysis on the performance of a 5-level cascaded H-bridge multilevel inverter (CHMI) based on a multi-carrier sinusoidal pulse width modulation (MSPWM) control technique. Performance analysis are made based on the results of a simulation study conducted on the operation of the CHMI using MATLAB/Simulink. The performance parameters chosen in the work include the waveform pattern, harmonic spectrum, fundamental value,and total harmonic distortion (THD) of the three-phase CHMI output voltage. From the results of the simulation study and the analysis conducted, several distinct features of the three-phase 5-level CHMI employing the MSPWM control scheme, in particular the phase disposition (PD) type of the carrier disposition (CD) method from the aspect of line voltage have been identified.